110. Transcranial direct current stimulation effects on single and paired flash visual evoked potentials. Issue 1 (January 2015) - Strigaro, G.; Mayer, I.; Chen, J.C.; Falletta, L.; Varrasi, C.; Rothwell, J.; Cantello, R.
<x xml:space="preserve">Abstract</x> Transcranial direct current stimulation (tDCS) has controversial effects on visual cortex. Paired-flash-visual evoked potentials (paired-F-VEPs) express neural inhibition within the visual system. Aim of this study was to evaluate the changes of single- and paired-F-VEPs during and after tDCS in healthy humans. In 26 healthy volunteers, F-VEPs were recorded from occipital electrodes with closed eyes. Stimuli were single flashes, intermingled to flash pairs at the interstimulus interval of 125, 62.5, 50, 33.3, 16.6 and 11.1 ms. The single-F-VEP was split into a "main complex" and a "late response". As to paired stimuli, the "test" F-VEP emerged from electronic subtraction of the single-F-VEP to the paired-F-VEP. In experiment 1, the return electrode was on the scalp and we studied changes in F-VEPs after anodal, cathodal (1 mA, 15 min) and sham tDCS. In experiment 2, VEPs were recorded before, during and after tDCS (anodal and cathodal) with the return electrode on the neck. In experiment 1, VEPs did not detect any significant change after tDCS. In experiment 2, anodal polarization increased the P2 latency and reduced the amplitude of the "late response" of the single-F-VEP. As for the paired-F-VEPs, no significant changes were detected. Low-intensity anodal tDCS has weak inhibitory aftereffects on the single-F-VEP and no effects on the paired-F-VEPs. Further methodological studies are needed to improve polarization efficacy.